HUBUNGAN MINAT BELAJAR DENGAN HASIL BELAJAR PENDIDIKAN AGAMA ISLAM PADA SISWA KELAS II SDIT AL-BASHIIRAH KARAWANG - Khonsa Mujahidah; Mujahidah, Maulida; Nur Fauziah; Ririn Dwi Wiresti (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to determine the relationship between learning interest and learning outcomes in Islamic Religious Education PAI in second-grade students of SDIT Al-Bashiirrah Karawang. This study uses a quantitative approach with a correlational method. The subjects of the study were all second-grade students of SDIT Al-Bashiirrah Karawang. Data on learning interest were obtained through a questionnaire compiled based on indicators of student interest, attention, and involvement in PAI learning. Data on learning outcomes were obtained from test scores or PAI learning evaluations. Data analysis was carried out using correlation techniques to determine the level of relationship between the two variabels. The results of the study indicate that there is a positive relationship between learning interest and PAI learning outcomes. Students who have high learning interests tend to achieve better learning outcomes compared to students who have low learning interests. This finding indicates that increasing learning interests needs to be a concern for teachers and schools as an effort to improve the quality of student learning outcomes, especially in Islamic Religious Education subjects.